2022
DOI: 10.1055/a-2005-3679
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic ultrasound in patients with resectable perihilar cholangiocarcinoma: impact on clinical decision-making

Abstract: Introduction Accurate assessment of the lymph node (LN) status is crucial in resectable perihilar cholangiocarcinoma (pCCA) to prevent major surgery in patients with extraregional metastatic LN (MLN). This study investigates the added value of preoperative Endoscopic Ultrasound (EUS) with or without Tissue Acquisition (TA) for the detection of MLN in patients with resectable pCCA. Methods In this retrospective, multicenter cohort study, patients with potentially resectable pCCA who underwent EUS preoperativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Malignancy was confirmed in 16% of nodes after tissue acquisition via EUS-FNA. Another retrospective multicentre cohort study demonstrated that EUS-FNA detected malignant lymph nodes in 14% of potentially resectable hCCA and avoided surgical exploration[ 73 ].…”
Section: Role Of Endobiliary Procedures In Diagnostic Evaluationmentioning
confidence: 99%
“…Malignancy was confirmed in 16% of nodes after tissue acquisition via EUS-FNA. Another retrospective multicentre cohort study demonstrated that EUS-FNA detected malignant lymph nodes in 14% of potentially resectable hCCA and avoided surgical exploration[ 73 ].…”
Section: Role Of Endobiliary Procedures In Diagnostic Evaluationmentioning
confidence: 99%